Security in a Web 2.0+ world : a standards based approach - Solari, C. (Carlos) (Wiley, 2009)
"Security for a Web 2.0+ World looks at the perplexing issues of cyber security, and will be of interest to those who need to know how to make effective security policy decisions to engineers who design ICT systems - a guide to information security and standards in the Web 2.0+ era. It provides an understanding of IT security in the converged world of communications technology based on the Internet Protocol. Carlos Solari and his team present much needed information and a broader view on why and how to use and deploy standards. They set the stage for a standards-based approach to design in security, driven by various factors that include securing complex information-communications systems, the need to drive security in product development, the need to better apply security funds to get a better return on investment"--Resource description page.